Effect of Preheating on Microstructure and Tensile Properties of Friction Stir Welded AA7075 Aluminium Alloy Joints - Poongkundran,R. (2016)
ABSTRACT The high strength AA7075 aluminum alloy is commonly used in the aerospace components due to its exclusive mechanical properties like lightweight and high strength. This alloy cannot be welded by fusion welding techniques due to solidification cracking which severely degrade the mechanical properties of the joint. In contrast, through friction stir welding (FSW) process solidification relate defects can be eliminated. Anyhow, the strength of friction stir welded joint is influenced by process parameters and tool parameters. These parameters govern the heat input, metal flow, microstructure evolution and mechanical properties of the weld. In normal welding condition, (without preheating) heat is generated by friction force which is produced between tool and workpiece. In this paper an added heat input through preheating the metal before weld. This preheating temperature effects on microstructure, microhardness and tensile properties of the joints were investigated. From this study the following conclusions are derived. Sufficient heat input should be given to obtain defect free and quality joint. The results showed that, preheating the base metal to 100 °C prior to welding improved the tensile strength and joint efficiency compared to the joints made without preheating.